Tuberculosis screening among Bolivian sex workers and their children - Silvia S. Chiang (Journal of Epidemiology and Global Health, 2019)
Bolivian sex workers were more likely than other employed women to report tuberculosis screening only if they reported HIV screening. Of all women with household tuberculosis exposure, <40% reported screening for themselves or their children. Coupling tuberculosis screening with sex workers’ mandatory HIV screenings may be a cost-efficient disease-control strategy.